(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Linguistics is a huge science that studies not only language per se, but also language and its relationship with society, with a person, with literature, etc. Neurolinguistics was born in the 1960s. The questions that neurolinguistics wants to answer were already formulated 200 years ago and several scientists developed this topic, but thanks to Chomsky’s Generative Linguistics, neurolinguistics has become a separate science. This article will focus on neurolinguistics, its history, its questions, its theories and models.